Modern Climate Policy: Moving beyond the market-liberal paradigm - Tom Krebs (Forum for a New Economy, 2023)
Traditional climate policy is based on the market-liberal paradigm that relies on carbon pricing, a belief in self-regulating markets, and transfer payments for the so-called "losers" of the transfor- mation process. The market-liberal approach to climate policy is certain to fail because it is based on a two-fold theory of society that is far removed from reality: it neglects adjustment costs in the trans- formation process and also economic power relations in the labor market. In contrast, modern climate policy takes into account these features of real societies and delivers green and inclusive economic growth. This policy is built on the idea of a forward-looking government that creates "pro-worker green institutions" and uses a "pro-worker green industrial policy" to support people and companies in the transformation process. The US Inflation Reduction Act (IRA) is an example of a modern climate policy in the sense that it includes several elements of a pro-worker green industrial policy. However, the US currently lacks the institutional structure to successfully implement a pro-worker climate agenda. European countries should embrace the general US approach to climate policy and develop their own, improved version based on their individual and institutional strengths.
Keywords: D52; J50; J64; L32; L50; O43; O44; Q43; Q50; 330; Climate Policy; Pro-Worker Green Industrial Policy; Pro-Worker Green Institutions; New Paradigm